1967
DOI: 10.1128/jb.93.4.1236-1241.1967
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance of Enteric Bacteria VIII. Chromosomal Location of Nontransferable R Factor inEscherichia coli

Abstract: The R21(TC) factor, obtained by transduction of the R1o(TC. CM. SM. SA) factor with phage e to group E Salmonella, is not transferable by the normal conjugal process. However, when R21(TC)+ transductants are infected with the F13 factor, the nontransferable R21(TC) factor acquires transmissibility by conjugation. R21(TC)+ conjugants of Escherichia coli K-12, to which only the R21(TC) factor was transmitted by cell-to-cell contact from an F' R4 donor, were still unable to transfer their R21(TC) factor by conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Drugs, determination of drug resistance, transmission of R and T-r factors by conjugation, conditions of transduction, and recombination of chromosomal markers were investigated as previously described [9,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs, determination of drug resistance, transmission of R and T-r factors by conjugation, conditions of transduction, and recombination of chromosomal markers were investigated as previously described [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…SM. SA) factor with phage epsilon [7] and is located on the host chromosome, between lac and pro, near lac [9]. or (TC.KM)-resistance, were sensitive to male phages and those carrying nontransferable drug-resistance were insensitive to male phages.…”
Section: Genetic Properties Of T95 Factormentioning
confidence: 99%
“…The F+ (tet) conjugants were capable of transmitting their (tet) determinant by conjugation but the F-(tet) conjugants were not [4]. When E. coli strain carrying the nontransmissible (tet) determinant was infected with F, F', R or T factors, the recombinants F-tet, F'-tet, R-tet and T-tet factors were formed [5,7,11,12,18]. These results strongly suggested.…”
mentioning
confidence: 99%
“…SM. SA) factor with phage P22 or epsilon, it was found that the resistance determinants were consistently segregated between the determinant for TC-resistance (tet) and the remaining resistance markers [6,17] and that the tet determinant was integrated into the host chromosome [2,8,9,11]. The nontransferable tet determinant obtained by transduction with phage epsilon was conjugally transferred to an E. coli K12 from Salmonella E strain by cooperation with F', F and the wild type R factor and the recombinants F-tet, F'-tet or R-tet were formed and transmissible by conjugation [7,10].…”
mentioning
confidence: 99%
“…The genetic symbols were described according to Taylor et al [16]. Transduction was conducted in the system of E. coli K12 and phage Plkc, following methods described previously [7,10,11]. A donor strain of F-lac-tet, JE346 F-lac85 was found to be deficient in structural genes lac Y and lac Z.…”
mentioning
confidence: 99%